Parenteral multivitamins in hospitalized patients - Niken Puruhita (World Nutrition Journal, 2022)
Malnutrition, especially micronutrient malnutrition remain as major problems in hospitalized patients. Micronutrient malnutrition contributes to health status and recovery speed of patients. It may lead to poor wound healing and/or increasing the risk of complication which result in longer hospital stay or even, death. Critically or acutely ill patients who are in total parenteral nutrition therapy for longer period need intravenous micronutrients. Past publications reported Wernicke’s Beri-beri in patient who did not received vitamins along with total parenteral nutrition infusion after 4 weeks passed away regardless the amounts of macronutrients delivered.